Peningkatan Kemampuan Membaca Pemahaman Cerita Anak melalui Penggunaan Model Pembelajaran Visualization, Auditory, and Kinestethic (VAK) - Dwijayanti, Nora; Trisiana, Anita; Septonanto, Daniel Joko (RESEARCH FAIR UNISRI, 2021)
The aims of this research to improve the ability of reading comprehention children’s story through the use of learning models Visualization, Auditory, and Kinestethic (VAK). The type of research and the approach used is Classroom Action Research which is held in stages up to two cycles. The research procedure is also carried out in stages starting from planning, then continuing on the implementation of cycles I and II, observing, and ending with reflection activities. Non-test data collection techniques with observations, documentation, and interviews. The test technique was carried out from the results of the evaluation of the pre-action test, cycle I, and graded in cycle II. Students' learning completeness in the pre-cycle is 74.5% with an average of 76.5%, then in the first cycle it is 72.5% with an average number of 78.15 and in the second cycle it is 83.5% with an average number of 85.25. Therefore, the success obtained in this classroom action research was completed in cycle II.